KUALITAS PELAYANAN DI RESTAURANT HOTEL GRAND SAVERO BOGOR - Erwin Setiawan; Kevin Daffa Fadlurrohman (Bajang Institute, 2024)
In this study, the focus on the restaurant is one of the outlets in the FB Hotel Grand Savero Bogor department which focuses on food and beverage services, both for guests who stay at the hotel or guests who come from outside and do not stay at the hotel. Service quality is a commitment and responsibility of management and all employees of Lotus Restaurant Hotel Grand Savero Bogor. The effort that can be made to provide services is to know and understand how the actual needs and expectations of these consumers are. Lotus Restaurant Hotel Grand Savero Bogor is one of the choices for culinary lovers in Bogor City. Tasting food at the hotel's restaurant is one of the fun activities to do, because the menu served is classy dishes, each of which has its own characteristics. This study uses a Likert scale by distributing questionnaires. Keywords: Quality of Service, Tangibles (physical evidence), Empathy (concern), Reability (reliability), Responsiveness (responsiveness), Assurance (Guarantee). F&B Department. Restaurant